Nigellidine (Nigella sativa, black-cumin seed) docking to SARS CoV-2 nsp3 and host inflammatory proteins may inhibit viral replication/transcription and FAS-TNF death signal via TNFR 1/2 blocking. Issue 22 (17th November 2022) - Banerjee, Amrita; Kanwar, Mehak; Das Mohapatra, Pradeep Kr.; Saso, Luciano; Nicoletti, Marcello; Maiti, Smarajit
Abstract: Tissue damage occurs in COVID-19 patients due to nsp3-induced Fas-FasL interaction/TNF-related apoptosis. Presently, possible therapeutic-drug, nigellidine against was screened by bioinformatics studies COVID-19. Atomic-Contact-Energy (ACE) and binding-blocking effects were explored of nigellidine ( Nigella sativa L.) in the active/catalytic sites of viral-protein nsp3 and host inflammatory/apoptotic signaling-molecules Fas/TNF receptors TNFR1/TNFR2. A control binding/inhibition of Oseltamivir to influenza-virus neuraminidase was compared here. In AutoDock, Oseltamivir binding-energy (BE) and inhibition-constant (KI) was −4.12 kcal/mol and 959.02. The ACE values (PatchDock) were −167.02/-127.61/-124.91/-122.17/-54.81/-47.07. The nigellidine BE/KI with nsp3 was −7.61 and 2.66, respectively (ACE values were −221.40/-215.62/-113.28). Nigellidine blocked FAS dimer by binding with a BE value of −7.41 kcal/mol. Its strong affinities to TNFR1 (-6.81) and TNFR2 (-5.1) are demonstrated. Our present data suggest that nigellidine may significantly block the TNF-induced inflammatory/Fas-induced apoptotic death-signaling in comparison with a positive-control drug Oseltamivir. Further studies are necessary before proposing nigellidine as medical drug. Graphical abstract: UF0001